Organizational decisions in multistage production processes - Verena Nowak (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
Organizational decisions in multistage production processes are often not made by the downstream headquarter firm, but by the various intermediate inputs suppliers along the value chain themselves. We assume a production process with one headquarter (final good producer) and two suppliers at different positions within the chain. In this environment with incomplete contracts and relationshipspecific investments, the firm decides only on the organizational form of her direct supplier, who in turn decides whether to outsource or to vertically integrate his own supplier. We find that the producer's and the supplier's organizational decisions are interrelated, particularly when production decisions occur sequentially. For instance, our model predicts that a higher technological importance of the downstream supplier raises the probability that the upstream supplier is vertically integrated. We also compare our model to the framework by Antras and Chor (2013) who assume that the headquarter makes all organizational decisions along the value chain. Then, we assume firms to be able to freely decide on their organizational decision structure and find for instance that firms with a higher overall productivity are more likely to choose a structure where the suppliers decide themselves on their suppliers' organizational forms.
Keywords: D23; L23; 330; outsourcing; vertical integration; property rights; sequential production processes